Juridical Review of Judicial Considerations in Deciding Tax Criminal Cases (Case Study of Decision No. 582/Pid.Sus/2023/PN.Jkt.Sel) - Diaz, Stella Maris; Fallo, Debi F.Ng.; Dede, Ngongo (Journal of Law and Economics, 2025)
This study analyzes the judicial review of judge's considerations in deciding tax criminal cases (Case Study of Decision No. 582/Pid.Sus/2023/PN.Jkt.Sel). The research employs normative legal research methodology. The study utilizes statutory approach and case approach. Data collection method relies on library research. The analysis of legal materials applies prescriptive-normative analytical techniques. The research findings reveal that the application of substantive criminal law in tax criminal case Decision No. 582/Pid.Sus/2023/PN.Jkt.Sel, specifically the application of substantive law against defendant Hijrah Saputra as stated in the first subsidiary indictment by the public prosecutor, was not appropriately implemented based on the panel of judges' considerations linked to various evidence presented during the trial. The panel of judges ruled that defendant Hijrah Saputra was legally and convincingly proven guilty of committing continuous tax crimes as regulated under Law Number 6 of 1983. The legal considerations by judges in imposing sentences incorporated both juridical and non-juridical factors. Juridical considerations examined facts discovered during the trial, including the public prosecutor's indictment, defendant's testimony, witness statements, expert testimony, and evidence. Non-juridical considerations were based on the defendant's background, accountability capacity, and resulting consequences. The panel of judges should have strengthened their considerations, particularly regarding aggravating circumstances.